The Playground is Alive: Online Games and the Formation of a Virtual Subculture - Gubagaras, Mark Anthony B.; Morales, Neil Jerome C.; Padilla, Stephen Norries A.; Zamora, Jun Daryl N. (Plaridel Journal of Communication, Media, and Society, 2008)
Online games have gained significant following from Filipino gamers. In this study, the researchers argue that the involvement of the gamers have led to the formation of a virtual subculture, which is composed mainly of the youth. To frame this study, three communication theories were used to explain the online gaming phenomenon. Three qualitative methods were used to gather necessary data: a key-informant interview with a local game developer, focus group discussions with gamers, and participant observation wherein the researchers played with other gamers while observing the online environment. From the data gathered, the researchers were able to find out how gamers define, form and recreate the virtual subculture, as well as how their online identities and the ideas they share help maintain, sustain, develop and expand the said subculture. As this research aims to provide a holistic approach to online gaming, suggested areas for future research and some practical recommendations are also discussed.